Impact of stretching on the performance and injury risk of long-distance runners - Baxter, C.; Mc Naughton, L. R.; Sparks, A.; Norton, L.; Bentley, D. (Research in Sports Medicine, 2017)
Stretching, either prior to exercise or at the end, or both, is typically carried out by all individuals undertaking sporting activity whether they be elite or recreational athletes. The many forms of stretching available to the athlete, either passive or active, have long been thought to improve performance, decrease injury and generally be advantageous to the athlete. This review examines the current state of the literature and evaluates what athletes can and should do with respect to this controversial topic.